Numerical Investigation and Analysis of Intermediate Principal Stress Effects on Rock Failure Behaviors - Shuxin Deng; Yonglai Zheng; Cuizhou Yue; Le Van Tuan (Advances in Civil Engineering)
A series of numerical experiments have been conducted to investigate the intermediate principal stress effects on rock failure behaviors. The numerical results show that the strength and deformation of the rock samples are significantly affected by the intermediate principal stress. The effects are inconsistent in different intervals. As intermediate principal stress ratio b increases, the rock strength increases initially and finally decreases. When b is approximately equal to 0.5, the strength of the rock sample reaches the maximum. In the microlevel, the intermediate principal stress affects the number and distribution of microcracks. The increase of the intermediate principal stress makes the projection of the microcracks on the loading plane change from uniform to uneven. On the one hand, the intermediate principal stress restricts the propagation of microcracks in the normal direction along the intermediate principal stress (or with a component in this direction), which will lead to an increase in the strength of the rock samples. On the other hand, the propagation of microcracks along the normal direction with small principal stress (or with a component in this direction) is promoted, which leads to a decrease in the strength of the rock sample. End friction can make the intermediate principal stress effect more significant because the friction of the loading end to the rock sample can result in stress deviation between the actual value and experimental value. Inhomogeneity of stress field induced by the change of stress states or end friction forces is the external factor of the intermediate principal stress effect. Also, the inhomogeneity of rock material itself is the internal factor. Intermediate principal stress will promote or restrict the failure of certain directions, thus affecting the overall strength of the rock samples. The numerical results can be very meaningful for stability analysis of rock masses in practical engineering.